Selection of Chlorella sp. from shrimp pond wastewater and determination of the optimal inoculum density for biomass production - Huỳnh, Ngọc Thanh Tâm; Phạm, Trường Lâm; Nguyễn, Thị Pha; Tran, Huu Hau (Hue University Journal of Science: Natural Science, 2026)
Microalgae is a rich source of protein, lipids, minerals, and vitamins. They could be employed as an extra food source for animals. However, there are still a lot of problems with selecting and culturing strains that have a lot of biomass potential. The study selected the TV1 strain from shrimp pond effluent because it grew the fastest among the seven microalgae strains isolated on Conway medium. Morphologically, the cells are spherical, with a diameter of 3 to 5 µm. The 18S rRNA gene sequence analysis and its comparison with the NCBI database classified the TV1 strain as belonging to the Chlorophyceae class and the Chlorella genus. Chlorella sp. TV1 is cultured in three stages. The primary culture propagation was carried out at a cell density of 0.313x106 cells/mL. The second and third subculture stages were carried out over 9 days, with initial cell densities of 0.634×106 and 0.452×106 cells/mL, respectively. The study selected the Chlorella sp. strain TV1 from shrimp pond wastewater, and finding a beneficial way to cultivate it will help produce a large amount of microalgae biomass. Further research is needed to improve animal husbandry environments and determine the effectiveness of wastewater treatment, with the goal of using it in circular agriculture.